Efektivitas Kombinasi Pijat Laktasi dan Pijat Oksitosin terhadap Fisiologis Produksi ASI pada Ibu Postpartum - Kurniati, Yuli bahriah, Yuni (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
Exclusive breastfeeding is the dream of every postpartum mother, but the problem of irregular breast milk production often becomes an obstacle. The combination of lactation massage and oxytocin massage is a potential non-pharmacological intervention to stimulate the hormones prolactin and oxytocin to increase breast milk production. This study aims to determine the effectiveness of the combination of lactation massage and oxytocin massage on the physiology of breast milk production in postpartum mothers. The quasi-experimental research method with a two-group pretest-posttest design involved 36 respondents selected through purposive sampling (n = 18 per group). Data were tested for normality with Shapiro-Wilk and analyzed using Paired T-Test and Independent Samples T-Test. The results of the Paired T-Test in the control group showed no significant difference (p = 0.331), while the experimental group showed a significant increase (p = 0.000) after the intervention. The results of the Independent T-Test showed no initial difference between the two groups at pretest (p=0.179), but a significant difference at posttest (p=0.002), with the intervention group having an advantage. In conclusion, the combination of lactation massage and oxytocin massage is significantly effective in increasing breast milk production in postpartum mothers. This intervention can be a standard non-pharmacological supportive therapy to support the success of exclusive breastfeeding programs.. Keywords : Lactation Massage, Oxytocin Massage, Physiology of Breast Milk Production